The Flexible Role of Middlemen in the Nutmeg Distribution Scheme in Maluku - baso, avryana; Dana, I Gusti Ngurah Krisna; Syamsuri, Ulfa Aulia (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2022)
Nutmeg cultivation in Banda Neira integrally involves middlemen, brokers who connect nutmeg farmers with the global market. Studies of such middlemen tend to emphasise the negative effects of their relationship with farmers. However, some research on their positive impact has also been conducted. This study seeks to explain the positive effects of middlemen by describing the flexibility of the brokered system. This descriptive-qualitative research, using data sourced from a study of the literature as well as interviews with resource persons, finds that flexibility has been created with the support of a communal social system that has carefully been maintained by middlemen in the nutmeg distribution scheme and supply chain. In the nutmeg distribution scheme, farmers have the option to sell nutmeg to a private actor—PT Kamboti —, but this option is not accessible to all smallholders because of the company’s profit-oriented (market) logic. This study concludes that middlemen play a flexible role, one which is positively and highly related to the social context that they have helped create and maintain. These middlemen tend to present themselves as the brothers, or at least relatives, of the farmers. As these middlemen prioritise social approaches to increase social bonding, there is no resistance to their involvement in the nutmeg distribution scheme in Maluku.